Simultaneous NICER and NuSTAR Observations of the Ultracompact X-Ray Binary 4U 0614+091 - D. L. Moutard; R. M. Ludlam; J. A. García; D. Altamirano; D. J. K. Buisson; E. M. Cackett; J. Chenevez; N. Degenaar; A. C. Fabian; J. Homan; A. Jaodand; S. N. Pike; et al. (The Astrophysical Journal, 2023)
We present the first joint NuSTAR and NICER observations of the ultracompact X-ray binary 4U 0614+091. This source shows quasiperiodic flux variations on the timescale of ∼days. We use reflection modeling techniques to study various components of the accretion system as the flux varies. We find that the flux of the reflected emission and the thermal components representing the disk and the compact object trend closely with the overall flux. However, the flux of the power-law component representing the illuminating X-ray corona scales in the opposite direction, increasing as the total flux decreases. During the lowest flux observation, we see evidence of accretion disk truncation from roughly 6 gravitational radii to 11.5 gravitational radii. This is potentially analogous to the truncation seen in black hole low-mass X-ray binaries, which tends to occur during the low/hard state at sufficiently low Eddington ratios.